The Influence of Game Based Teaching Method with Binggo Games and Learning Motivation on Student Learning Outcomes in Elementary School - Hartani, B. Sri; Nuraini, Nuraini; Marhamah, Marhamah (Sumber Belajar Sejahtera, 2025)
This study aims to examine the effect of the application of the game based learning (GBL) method with binggo games and learning motivation on student learning outcomes in Indonesian learning in elementary schools.metpde the research used is quantitative with a pseudo-experimental approach using the Treatmen by level 2x2 design. The research was carried out on grade I students at SD Negeri 1 Terara with a total population of 40 students, the sample was determined through stratified random sampling based on the categories of high and low learning motivation. The instruments used include learning outcome tests and learning motivation questionnaires, and data analysis using two-way ANAVA. The results of the study revealed that: (1) There is an influence of the Game Based Learning Method with Binggo Toys on Learning Outcomes, (2) There is a correlation between the Game Based Learning (GBL) method on learning outcomes (3) There are Indonesian Learning Outcomes in Game Based Learning LearningWith the Binggo game, learning outcomes and direct learning are higher for highly motivated students in elementary school. (4)There are Indonesian learning outcomes in game based learning with lower Binggo games and direct learning outcomes for low-motivation students in elementary school